As I Remember: Theodore Matthew (1967)
George P. Cooper's interview with Theodore Matthew, a former faculty member of the physical sciences department at Cal Poly from 1948 to 1962. [00:00:10] As I Remember Opening [00:00:23] Matthew recalls his first meeting with a representative of Cal Poly [00:01:31] Matthew describes his experience upon arriving at Cal Poly [00:02:37] Matthew describes the temporary buildings present in 1948-49 [00:04:45] Matthew describes the temporary student housing in 1948-49 [00:05:43] Matthew recalls the changes that occurred in 1949-50, such as the development of the library building and increases in temporary student housing [00:07:42] Matthew discusses the changes that took place in 1959-60, such as larger dormitories and the development of a new science area [00:08:26] Matthew describes the new science building complex [00:09:27] Matthew describes how the staff went about determining what facilities they needed [00:09:57] Matthew discusses the addition of new buildings in 1961, such as the construction of a dining complex, gymnasium, and theater [00:12:13] Matthew describes the growth of the staff in the physical sciences department [00:12:58] Matthew recalls his role in the development of the "college counsel," a group that would represent the faculty [00:15:57] Cooper describes the current state of the faculty/staff counsel [00:16:53] Matthew describes his role in the state employees' organization [00:18:19] Matthew the difference between the problems of civil service employees and those of teachers [00:18:55] Matthew discusses his role in the Disaster Committee [00:20:52] Matthew discusses some of the details of the disaster plan as well as its use in other areas [00:23:19] Matthew discusses what he's being doing since he's retired [00:25:39] As I Remember Closing